Which boundaries? How mobility networks across countries and status groups affect the creative performance of organizations - Shipilov, Andrew; Godart, Frédéric C.; Clement, Julien (Strategic Management Journal, 2017)
Research summary : Losing key employees to competitors allows an organization to engage in external boundary‐spanning activities. It may benefit the organization through access to external knowledge, but may also increase the risks of leaking knowledge to competitors. We propose that the destination of departed employees is a crucial contingency: benefits or risks only materialize when employees leave for competitors that differ from the focal organization along significant dimensions, such as country or status group. In the context of the global fashion industry, we find that key employees' moves to foreign competitors may increase (albeit at a diminishing rate) their former employers' creative performance. Furthermore, firms may suffer from losing key employees to higher‐ or same‐status competitors, but may benefit from losing them to lower‐status competitors. Managerial summary : Losing key employees to competitors can provide organizations with access to external knowledge, but increase risks of leaking knowledge to competitors. We find that an organization's access to external knowledge and its risks of knowledge leakage through employee mobility may be affected by whether its employees leave for competitors in a foreign country or in a different status group. In the context of the global fashion industry, we show that key employees' moves to foreign competitors increase (up to a point) their former employers' creative performance. Furthermore, firms may suffer from losing key employees to higher‐ or same‐status competitors, but benefit from losing them to lower‐status competitors. Hence, executives in creative industries and possibly beyond could welcome losing employees to competitors in foreign countries or to lower‐status competitors . Copyright © 2016 John Wiley & Sons, Ltd.